KONTRIBUSI IKLIM KERJA DAN INSENTIF TERHADAP KEPUASAN KERJA GURU SMK SWASTA DI BUKITTINGGI - Susanti, Dessi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
Based on observations while private Vocational School in Bukittinggi, it appears the low level of job satisfaction of teachers. It is visible from most of the teachers who often complain, upset, not happy in their duties as teach subjects that are not in accordance with their expertise. This study aims to reveal 1) Contributions of working climate on job satisfaction of teachers, 2) Contributions of incentives on job satisfaction of teachers, 3) Contributions of working climate and incentives on job satisfaction of teachers. Subjects in this study were all private vocational school teachers having the status as civil servants in Bukittinggi with 279 teachers. The sampling technique in this study was stratified proportional random sampling consisting of 73 teachers. The results showed that: 1) work climate contribute significantly on job satisfaction of teachers of private vocational in Bukittinggi at 46.10%; 2) Incentives contribute significantly on job satisfaction of private vocational teachers in Bukittinggi at 38.80%; and 3) work climate and incentives together contribute significantly to job satisfaction private vocational school teachers in Bukittinggi at 56.90%. Keywords: work climate, incentives, work satisfaction.